Current practice of preparing morphine infusions for nurse/patient-controlled analgesia in a UK paediatric hospital: healthcare professionals' views and experiences. Issue 6 (5th April 2016) - Rashed, Asia N; Tomlin, Stephen; Forbes, Ben; Whittlesea, Cate
Abstract : Objective: To explore the views and experiences of healthcare professionals (HCPs) regarding the preparation of morphine infusions for nurse/patient-controlled analgesia (N/PCA). Methods: Three focus groups were conducted with HCPs (anaesthetists, nurses in theatres and wards) at one UK children's hospital. Focus groups were transcribed verbatim and content analysis was used to identify themes. Results: A variety of approaches are used to prepare morphine infusions. A lack of appreciation of the excess volume present in morphine ampoules that nominally contain 1 or 2 mL was identified. Other sources of error were miscalculation, complexity of the multistep procedure, distractions and time pressure. Participants suggested that 'ready-to-use' prefilled syringes and preprogrammed syringe pumps would improve practice and minimise the risk of error. Conclusions: Risks associated with the preparation of infusions for paediatric N/PCA, in particular non-appreciation of the overage (excess volume) in morphine ampoules, raise concerns about the accuracy of current practices.